Role of lignin and thermophilic lignocellulolytic bacteria in the evolution of humification indices and enzymatic activities during compost production. (1st January 2021) - Hemati, Arash; Aliasgharzad, Nasser; Khakvar, Reza; Khoshmanzar, Elaheh; Asgari Lajayer, Behnam; van Hullebusch, Eric D.
Highlights: Thermophilic lignocellulolytic bacteria are effective in accelerating and improving compost indices. High lignin treatments require more time to produce compost in comparison with low lignin treatments. Enzymatic and humification indices can be utilized rather than outdated methods. Abstract: This study aimed to evaluate the effect of lignin content and thermophilic lignocellulolytic bacteria bioaugmentation on composting process. Treatments including bioaugmentation with thermophilic lignocellulolytic bacteria isolates such as Paenibacillus validus, Paenibacillus koreensis, Bacillus nealsonii, a mixture of the three mentioned bacterial isolates and control were compared at two level of organic media (high lignin content and low lignin content) in the form of nested factorial design. Several indices such as humification and enzymatic activities were monitored to evaluate the composting rate. The results revealed that high lignin treatments displayed higher ligninase, xylanase, protease and urease enzymatic activities compared to low lignin treatments. On the other hand, low lignin treatments showed higher level of humification indices, cellulase, beta-glucosidase and alkaline phosphomonoesterase enzymatic activities in comparison with high lignin treatments. Also, all measured enzymatic activities are at their highest between the second and the tenth weeks; however, this trend decreased to reach a steady point from the 18th weeks to the 24th weeks, but for urease enzymatic activity, a totally different trend in high and low lignin treatments was observed. Moreover, the highest humification indices as well as the cellulase and β-glucosidase enzymatic activities were associated to the Bacillus nealsonii isolate and the full consortium. They also displayed the highest ligninase, xylanase, protease, and urease and phosphatase activities. The efficient isolates shortened the time required for completing the composting process for about 2 to 4 weeks compared to the control treatments. For all measured indices, the control treatment had the lowest values.